Probing Vulnerability of the gp41 C-Terminal Heptad Repeat as Target for Miniprotein HIV Inhibitors. Issue 20 (18th September 2020) - Jurado, Samuel; Moog, Christiane; Cano-Muñoz, Mario; Schmidt, Sylvie; Laumond, Géraldine; Ruocco, Valentina; Standoli, Sara; Polo-Megías, Daniel; Conejero-Lara, Francisco; Morel, Bertrand
Abstract: One of the therapeutic strategies in HIV neutralization is blocking membrane fusion. In this process, tight interaction between the N-terminal and C-terminal heptad-repeat (NHR and CHR) regions of gp41 is essential to promote membranes apposition and merging. We have previously developed single-chain proteins (named covNHR) that accurately mimic the complete gp41 NHR region in its trimeric conformation. They tightly bind CHR-derived peptides and show a potent and broad HIV inhibitory activity in vitro . However, the extremely high binding affinity (sub-picomolar) is not in consonance with their inhibitory activity (nanomolar), likely due to partial or temporal accessibility of their target in the virus. Here, we have designed and characterized two single-chain covNHR miniproteins each encompassing one of the two halves of the NHR region and containing two of the four sub-pockets of the NHR crevice. The two miniproteins fold as trimeric helical bundles as expected but while the C-terminal covNHR (covNHR-C) miniprotein is highly stable, the N-terminal counterpart (covNHR-N) shows only marginal stability that could be improved by engineering an internal disulfide bond. Both miniproteins bind their respective complementary CHR peptides with moderate (micromolar) affinity. Moreover, the covNHR-N miniproteins can access their target in the context of trimeric native envelope proteins and show significant inhibitory activity for several HIV pseudoviruses. In contrast, covNHR-C cannot bind its target sequence and neither inhibits HIV, indicating a higher vulnerability of C-terminal part of CHR. These results may guide the development of novel HIV inhibitors targeting the gp41 CHR region. Graphical Abstract: Unlabelled Image Highlights: Design, production and characterization of mini protein HIV inhibitors Engineered disulfide bond increases conformational stability. Protein stabilization enhances inhibitory capacity. NHR coiled-coil of gp41 is composed of two subdomains with different conformational stability. Vulnerability of the gp41 CHR region as inhibition target.